HUBUNGAN MOTIVASI KERJA DENGAN PERILAKU NELAYAN PADA USAHA PERIKANAN TANGKAP - Helena Tatcher Pakpahan; Richard W. E. Lumintang; Djoko Susanto (Jurnal Penyuluhan, 2006)
Community of fishermen is one of social segments who considered as having daily life worse than other social segments, such as farmers, factory labourers, etc. Certain efforts can be done to improve the level of life of the fishermen, i.e to increase their production of fish. The way which can be done is by improving the unit of productive assets so that it can increase motivation of the fishermen for better behavior. Recently fishermen are not able to go out from their miserable socio economic situation, mainly due to (a) bargaining position weakness, (b) lacking of capital, (c) low level of knowledge and skill, (d) lacking of supervision, (e) no guarantee of promising market. Based on those evidence it is worth to study the relationship between fishermen motivation and their behavior to increase production of fish.